HOLOCENE PALEOENVIRONMENTAL RECORDS FROM NIKOLAY LAKE, LENA RIVER DELTA, ARCTIC RUSSIA - Andreev A.; Schwamborn G.; Rachold V.; Hubberten H.-W.; Tarasov P.; Ilyashuk B.; Ilyashuk E.; Bobrov A.; Klimanov V. (My University, 2004)
Radiocarbon-dated pollen, rhizopod, chironomid and total organic carbon records from Nikolay Lake (73°20’N, 124°12’E), complemented by a pollen records from nearby peat sequence, provide the detailed environmental reconstruction for the Holocene in the Lena Delta area. Shrubby Alnus fruticosa and Betula exilis tundra existed during 10,300-4800 cal. yr BP, and gradually disappeared after that time. Climate reconstructions based on the pollen and chironomid records suggest that climate during ca 10,300-9200 cal. yr BP was up to 2-3°C warmer than nowadays. Pollen-based climate reconstructions show that climate was relatively warm during 9200-6000 cal. yr BP, and rather unstable between ca 5800-3700 cal. yr BP. Both qualitative interpretation of pollen data and results of quantitative reconstruction imply that climate and vegetation became similar to modern-day conditions after ca 3600 cal. yr BP. Сhironomid-based temperature reconstruction suggests a relatively warm period between ca 2300 and 1400 cal. yr BP, corresponding with slightly warmer climate reconstructed from the pollen. The modern chironomid and rhizopod assemblages established after ca 1400 cal. yr BP.
Keywords: Holocene; Lake sediments; Biological records; Climate and vegetation history; East Siberian Arctic; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен